An analysis in vivo of intracanal bacterial load before and after chemo-mechanical preparation: A comparative analysis of two irrigants and two activation techniques - Rico Romano, Cristina; Zubizarreta Macho, Álvaro; Baquero Artigao, María Rosario; Mena Álvarez, Jesús (My University, 2016)
Background: The goals of this randomized double-blind trial were to assess the antimicrobial activity in vivo of Sodium hypochlorite (NaOCl) vs. chlorhexidine gluconate (CHX) used in combination either with EndoActivator® or IRRI S® files in patients with apical periodontitis. Material and Methods: A total of 120 patients with apical periodontitis (in single or multiple root canals) were randomly assigned to the four irrigation protocols outlined below: Group A: 5.25% sodium hypochlorite (NaOCl) + EndoActivator®; Group B: 5.25% NaOCl + IRRI S® files; Group C: 2% chlorhexidine gluconate (CHX) + EndoActivator®; Group D: 2% CHX + IRRI S® files. Paper points were used to collect microbiological samples before (1A samples) and after (1B samples) irrigation. Viable colony-forming units (CFU) were quantified twice: (1) without speciation, and (2) only for Enterococcus Faecalis (EF). Statistical analysis was performed using SPSS 22.0 for Windows. Results: No significant differences were observed between NaOCl and CHX in the reduction of CFU; in fact, reduction was > 93% for the two irrigants. Conversely, statistically significant differences were found between the two activation techniques (sonic and ultrasonic) in the reduction of Enterococcus faecalis (EF). Thus, the effectiveness of ultrasonic activation was significantly higher (> 93%; p=0.012) as compared to sonic activation. Following the combination of the two irrigants with the two activation techniques (groups A, B, C and D), significant differences were observed between group A and B (p=0.025) in the reduction of EF populations, reaching up to 94%. Conclusions: NaClO and CHX are effective in reducing intracanal bacterial load. Ultrasonic activation is the most effective activation technique in reducing EF populations.